Endogenous Financial Structure and the Transmission of ECB Policy - Ivo J.M. Arnold; Casper G. de Vries (Tinbergen Institute, 1999)
There is a widely held view that existing differences in the capital and moneymarket structures across EMU countries are an important matter of concern forthe ECB, because they might hinder the uniform transmission of monetary policyactions. We argue that many aspects of financial structure are endogenous to themonetary policy regime in place. It is shown that capital market structures areheavily correlated with past inflation and inflation uncertainty.Since the EURO regime imposes a unified monetary policy, we suspect that thedifferences will wither. A single currency, a single money market rate and a uniformreserve requirement will rapidly harmonize the money markets. In sum, wepredict that differential responses in the transmission of monetary policy actionsthrough the money and capital markets are of minor concern for theECB.
Keywords: 330; Eurozone; Geldpolitik; Geldpolitische Transmission; EU-Staaten